Text-based Character in Teaching Reading: Do Students Can Achieve Significant Result in Reading Test? - Hasan Hasan; Andi Sadapotto; Muhammad Hanafi; Usman Usman (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
This quasi-experimental study involves the experimental and control group which consist of 60 students in first year of SMA Muhammadiyah Sidenreng Rappang 2019/2020 academic year. The reading test is used to collect data to find out do the students can achieve significant result in reading test using Text-based Character. Based on the result the mean score of the experimental group pre-test was 72.67 and classified into good classification, while the control group was 69.63 classified into good. The mean score of the post-test after treatment for the experimental group was 82.43 (very good) while the control group was 76.53, (good) classification still. The researcher found that the T-table is higher than the t-test (α) (1.659<2.021). It means that there is a significant difference in the pre-test of the control and experimental group, while in post-test of an experimental and control group, the researcher finds that the T-test is higher than the alpha and previous score in the the pre-test (α) (3.089>2.021). The degree of freedom is 58. This study reveals that the alternative hypothesis (H1) was accepted, and the null hypothesis (H0) was rejected. This is means that the use of Text-based Characters can improves students' reading skills in significant way.